The impacts of (Ba,Sr)3BP3O12:Eu2+ on the luminous flux of phosphor-converted-white light emitting diode packages - Van Liem Bui; Dieu An Nguyen Thi (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The use of (Ba,Sr)3BP3O12:Eu2+ in the remote phosphor structure has been proposed and analysed to offer significant improvement to the lighting performance of the phosphor-converted white light emitting diode (LED). The phosphor emits green and blue spectra centred at 520 nm and 465 nm, respectively. Thus, the phosphor can compensate the blue and green light energy components in the white-light spectral band, helping to enhance the luminous efficiency and colour uniformity of the dual-layer remote phosphor package. The increase in (Ba,Sr)3BP3O12:Eu2+ however is not advantageous to the colour rendering index because of the lower red emission. The backscattered and back-reflected lights are degraded when the (Ba,Sr)3BP3O12:Eu2+ phosphor layer appears in the structure. The stable chromaticity and luminous flux at good values are observed when 10% weight percentage of (Ba,Sr)3BP3O12:Eu2+ is applied.